Clear Cell Carcinoma Arising in Vulvar Endometriosis. (26th July 2018) - Buppasiri, Pranom; Kleebkaow, Pilaiwan; Tharanon, Chantip; Aue-aungkul, Apiwat; Kietpeerakool, Chumnan
Abstract : We report a case of vulvar clear cell adenocarcinoma in a woman presenting with a lump and pain in the right side of the labia majora. Three years prior to this visit, she underwent a total abdominal hysterectomy with bilateral salpingooophorectomy and excision of a labial mass. Pathological examination revealed adenomyosis and multiple leiomyomas in the uterus, endometriotic cysts in both ovaries, and foci of atypical endometriosis in the labial mass. The results of an incision biopsy performed before referral indicted only apocrine hidrocystoma. Physical examination revealed a hard mass at the right labia majora extending to the right groin. The mass seemed to be in continuity with the pubic symphysis that would require pubic bone excision and reconstruction with flap surgery to achieve complete resection. However, the patient refused such extensive surgery. Based on previous diagnosis of vulvar endometriosis, she had been treated with GnRH agonists and depot medroxyprogesterone acetate. However, the mass developed into an ulcer and increased in size. A second biopsy of the mass was undertaken, and the pathological diagnosis was clear cell carcinoma with coexisting atypical endometriosis. Computed tomography of the abdominopelvic region showed an ulcerative mass at the right labia majora and nodal metastasis at the external iliac and inguinal regions. Systemic chemotherapy was administered. The growth of the tumors stabilized during the first two cycles of chemotherapy but rapidly progressed thereafter. At 17 months after her initial presentation, the patient passed away due to the progression of the disease.